Floating Gate Memory‐based Monolayer MoS2 Transistor with Metal Nanocrystals Embedded in the Gate Dielectrics. Issue 2 (13th August 2014) - Wang, Jingli; Zou, Xuming; Xiao, Xiangheng; Xu, Lei; Wang, Chunlan; Jiang, Changzhong; Ho, Johnny C.; Wang, Ti; Li, Jinchai; Liao, Lei
<x xml:space="preserve">Abstract</x> Charge trapping layers are formed from different metallic nanocrystals in MoS2‐based nanocrystal floating gate memory cells in a process compatible with existing fabrication technologies. The memory cells with Au nanocrystals exhibit impressive performance with a large memory window of 10 V, a high program/erase ratio of approximately 105 and a long retention time of 10 years. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>